Hidrolisados proteicos: digestibilidade aparente dos nutrientes para a tilápia-do-Nilo (Oreochromis niloticus) - Souza, Herivelto Beck de (2024)
The increase in global animal protein production requires processing waste for technological and sustainable purposes. Waste from the fish and poultry slaughter chain corresponds to 11% and 30% of the total, respectively, and is a raw material with high nutritional quality and is referred to as co-products. Biotechnological solutions, such as the hydrolytic process, are emerging to fully utilize the nutrients available. The objective of the study was to evaluate the apparent digestibility coefficients (CDA) of protein (CDAPB), energy (CDAEB), and essential and non-essential amino acids of fish protein hydrolysates (HFP) (Chapter I) and chicken protein hydrolysate (PHF) (Chapter II) by juvenile Nile tilapia. The ADC was obtained from enzymatic hydrolysis using alcalase (0.5%) as protease and atomized by the spray dryer method. The PHF was produced by BRF Ingredients and incorporated different adjuvant substances in its composition. The physicochemical composition (dry matter – DM; crude protein – CP; gross energy – GE; essential and non-essential amino acids) of the test ingredients, feed, and fish feces were analyzed. The experimental diets were composed of 80% of the reference diet and 20% of protein hydrolysates, being HPF; PHF; PHF with maltodextrin (PHFMalto); PHF with yeast (PHFLevedura); and PHF with starch (PHFAmido). For the apparent digestibility test, juvenile Nile tilapia were randomly distributed in a system with water recirculation composed of cylindrical conical tanks (500 L), adapted with a feces collection cup. The animals were fed to apparent satiety five times a day at 8:00 a.m., 11:00 a.m., 1:00 p.m., 3:00 p.m., and 5:00 p.m., totaling 14 days of fecal collection. The indirect method of material collection was followed, using 0.1% chromium oxide III (Cr2O3) as an inert marker in the diets. Regarding HFP, the average values of CDAPB and CDAEB for HFP were 92.90% and 91.59%, respectively. The CDA for essential and non-essential amino acids were all high (>90%), except phenylalanine (77.93%). Regarding the PHFs, the mean values obtained for PHFMalto (97.85 and 96.24%) and PHFLevedura (98.39 and 97.98%) were lower than those for PHF without the use of adjuvants (99.77 and 100.00%), except the CDAEB of PHFMido (99.27 and 100.00%) (p<0.05). Significant differences were observed between the CDAs of the different protein hydrolysates evaluated (p<0.05) for practically all nutritional fractions analyzed, except for some amino acids such as phenylalanine, valine, glutamic acid and cystine (p>0.05). It is concluded that HFP presents high values of nutritional fractions of interest for aquaculture, such as crude protein content (92.46%) and tryptophan (0.71 g kg−1), in addition to high apparent digestibility rates for Nile tilapia. Furthermore, it is concluded that the inclusion of adjuvant substances in PHF presents an alternative for the composition of this product, since nutritional fractions of interest for aquaculture are made available, in addition to high apparent digestibility rates for Nile tilapia.